Digital Literacy- Based Case Method Lecture Model for Strengthening Student Critical Thinking - Filma Alia Sari; Fenny Fenny Trisnawati; Supentri Supentri; M. Yogi Riyantama Isjoni (STAI Hubbulwathan Duri, 2024)
The change in the learning paradigm from traditional learning models to digital literacy-based case methods involves several changes in habits, which ultimately require each individual to adapt and complete all activities from time to time. Therefore, digital competence is important in the learning process. Using good reading skills can support successful learning. Interest in reading books has decreased because it has been replaced by a new method, screen-based reading behavior. This has aroused researchers' interest in discussing the importance of digital literacy. The case method is the learning model that can support students' digital competence in participating in learning and improving critical thinking. This study employs a 4-D development paradigm (Four-D Models) to create cutting-edge goods in the shape of digital literacy-focused case study lecture model project modules. The produced product's feasibility is confirmed through the validation procedure and implementation test to ensure the creation of the final product. The study took place in Pekanbaru, Riau Province, between March and June 2023. The data analysis methods utilised included observation, documentation studies, interviews, FGDs, data reduction, analysis, data interpretation, and data triangulation. Conclusions can be derived from the outcomes of the data analysis. This digital literacy-based case method lecture innovation, initially designed for monetary economics lectures, can be applied across all courses to enhance critical thinking skills in other scientific disciplines and facets of life. We anticipate that this marks the commencement of advancements in lecture innovation and development.